2022
DOI: 10.1002/ijgo.14356
|View full text |Cite
|
Sign up to set email alerts
|

The effect of BNT162b2 SARS‐CoV‐2 mRNA vaccine on menstrual cycle symptoms in healthy women

Abstract: Objective To investigate the impact of the SARS‐CoV‐2 mRNA BNT162b2 vaccine on women’s menstural cycle. Methods In this questionnaire‐based cross‐sectional study, we assessed menstrual pattern and changes of women who completed the SARS‐CoV‐2 mRNA BNT162b2 vaccine three months before and after receiving the vaccine. Included were women aged 18‐50 without known gynecological comorbidities who regularly monitor their menstruation through electronic calendars. All particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
16

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 23 publications
0
9
0
16
Order By: Relevance
“…To date, although with less solid data, other consequences associated with the vaccines have been detected and reported. For example, alterations in the menstrual cycle such as abnormal bleeding and delayed menstruation following the second booster dose of the BNT162b2 vaccine [ 121 , 122 ]. Studies reporting the main adverse events are summarized in Table 2 .…”
Section: Advantages and Caveats Of Efficacy And Safety Of Mrna Sars-c...mentioning
confidence: 99%
“…To date, although with less solid data, other consequences associated with the vaccines have been detected and reported. For example, alterations in the menstrual cycle such as abnormal bleeding and delayed menstruation following the second booster dose of the BNT162b2 vaccine [ 121 , 122 ]. Studies reporting the main adverse events are summarized in Table 2 .…”
Section: Advantages and Caveats Of Efficacy And Safety Of Mrna Sars-c...mentioning
confidence: 99%
“…Another study from Israel has reported the worsening of dysmenorrhea in the cohort with and without endometriosis, but the information about positive improvement are is [ 16 ]. Additionally, another study has reported new incidence or worsening of dysmenorrhea by more than 47% of participants during the COVID-19 pandemic [ 17 ]. In contrast, there are also studies reporting reduced occurrence or improvement in their symptoms following COVID-19 vaccination, similar to our results [ 11 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there are also studies reporting reduced occurrence or improvement in their symptoms following COVID-19 vaccination, similar to our results [ 11 , 18 ]. However, the studies focusing on dysmenorrhea or back pain described above are very heterogenous regarding their methods; a few evaluated the intensity of the symptoms [ 16 , 17 ], others compared endometriosis patients vs. health controls [ 16 , 19 ], and only two of these studies followed the same approach that we used here and compared the occurrence of the symptoms before and after immunization [ 11 , 18 ]. The majority of our participants reported dysmenorrhea and back pain less frequently after immunization, but rarely, we also observed the reverse pattern, i.e., dysmenorrhea and back pain after but not prior to immunization, similar to our results regarding changes in menstrual bleeding reported elsewhere [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations